(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This study evaluated the soil physico-chemical properties and concentration of heavy metals (lead and chromium) and their influence on the soil and groundwater quality due to waste dumps in Owerri, Southeastern Nigeria. Four profile pits of about 180 cm depth were dug, one each at the polluted and control sites, from which soil samples were collected and analysed. Also, water samples proximate to the dumpsite (5 m) were collected, and control samples about 300 m away from the dumpsite were collected. Soil data were subjected to analysis of variance, and significant means were separated using the least significant difference (p≥ 0.05), while water samples were compared with local and international standards. The results obtained showed that the soils studied were dominated by sand (>80%). Soils from the polluted site had a higher soil pH (>6), whereas the unpolluted sites had a pH (<6.24). Soil organic matter, % total nitrogen, total exchangeable bases, bulk density, and electrical conductivity were higher in the Nekede polluted site (>180µS/cm) and least in the Nekede control site of Owerri. The control soil showed higher % silt content; % porosity, moisture content, and heavy metal concentration in the polluted soils were significantly higher than the control soils. This indicates a higher deterioration of both soil and water in the environment; thus, water pre-treatment before domestic or industrial use and remediation of the polluted soils before agricultural activities are recommended.